1999
DOI: 10.1038/16264
|View full text |Cite
|
Sign up to set email alerts
|

GABAA-receptor-associated protein links GABAA receptors and the cytoskeleton

Abstract: Type-A receptors for the neurotransmitter GABA (gamma-aminobutyric acid) are ligand-gated chloride channels that mediate inhibitory neurotransmission. Each subunit of the pentameric receptor protein has ligand-binding sites in the amino-terminal extracellular domain and four membrane-spanning regions, one of which forms a wall of the ion channel. Each subunit also has a large intracellular loop that may be a target for protein kinases and be required for subcellular targeting and membrane clustering of the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
585
2
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 732 publications
(603 citation statements)
references
References 21 publications
13
585
2
3
Order By: Relevance
“…The rat Map1LC3 was the first mammalian homologue of the yeast autophagosome-associated protein Apg8 to be identified besides GATE-16 (Golgi-associated ATPase enhancer of 16 kDa) and GABARAP (GABA A receptor-associated protein) (10,(17)(18)(19)(20). The significant sequence similarity between the rat and yeast proteins suggested that the molecular machinery involved in autophagy is highly conserved in eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…The rat Map1LC3 was the first mammalian homologue of the yeast autophagosome-associated protein Apg8 to be identified besides GATE-16 (Golgi-associated ATPase enhancer of 16 kDa) and GABARAP (GABA A receptor-associated protein) (10,(17)(18)(19)(20). The significant sequence similarity between the rat and yeast proteins suggested that the molecular machinery involved in autophagy is highly conserved in eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…Gephyrin also colocalizes with GABA A Rs in the intact brain, retina, and spinal cord (Levi et al, 1999;Fischer et al, 2000;Sassoe-Pognetto et al, 2000). Additionally, it has been proposed that gephyrin is involved in the postsynaptic clustering of GABA A Rs (Essrich et al, 1998;Kneussel et al, 1999), although no direct binding of GABA A Rs to gephyrin has been demonstrated and other proteins might also be involved in GABA A R clustering (Knuesel et al, 1999(Knuesel et al, , 2001Wang et al, 1999;Fischer et al, 2000;Kneussel et al, 2000Kneussel et al, , 2001.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, fragments corresponding to the cytoplasmic domain of the original bait [γ2(361-404)] or the M4 domain [γ2(405-428)] of the γ2 subunit also failed to interact. Absence of interaction between CAML and the two M4 domain-lacking γ2 fragments [γ2(361-404) and γ2(361-417)] is significant as both these constructs showed faithful interaction with a bait construct containing amino acids 36-117 of GABARAP, which is known to interact with the C-terminal end of the γ2 subunit cytoplasmic domain (Wang et al, 1999). Collectively, these data indicate that both the C-terminal 44 amino acids of the γ2 subunit major cytoplasmic loop region and the M4 domain are required for interaction with CAML.…”
Section: Caml Interacts With Cytoplasmic Loop and M4 Domains Of The γmentioning
confidence: 99%